Василий Суриков - Алленов Михаил Михайлович (Картинная галерея, 1998)
Экземпляры: (20230525) / Инвентарный номер: 25908 / Цена: 91.36 / Сис.шифр: 85.143(2)1 / Авт.знак: А 50 / ГРНТИ: 18 / ББК: 85.143(2)1